Cost‐conscious robotic restorative proctectomy has similar economic and oncologic outcomes to open restorative proctectomy: Results of a long‐term follow‐up study. Issue 6 (27th September 2021) - Cengiz, Turgut Bora; Benlice, Cigdem; Ozgur, Ilker; Kaya, Gizem; Aytac, Erman; Kalady, Matthew F.; Steele, Scott R.; Liska, David; Gorgun, Emre
Abstract: Background: In this study, we hypothesised that the direct hospital costs of robotic restorative proctectomy (RP) would be similar to those of open RP when a cost‐conscious approach was employed in rectal cancer patients. Methods: We included consecutive patients with rectal cancer who underwent RP between 12/2011 and 10/2014. A cost‐conscious approach was employed in robotic surgery. We compared demographics, long‐term oncologic outcomes, and direct hospital costs between the open and robotic groups. Results: There were 32 robotic and 68 open RP procedures performed. Compared to open RP, the robotic RP group had a longer operative time but less estimated blood loss, intraoperative transfusions, overall short‐term morbidity, decreased length of stay. After the initial five robotic cases, overall hospital costs were comparable between the groups (1 ± 0.5 vs. 1 ± 0.4, open and robotic RP, respectively, p  = 0.90). Conclusion: Increasing surgeon experience and a cost‐conscious approach may improve the value of care of robotic RP in patients with rectal cancer.